2009
DOI: 10.1258/jtt.2008.080803
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk for diabetes patients in a care coordination, home-telehealth programme

Abstract: We assessed a home monitoring/care coordination programme for veterans with diabetes. Patients enrolled in the programme (n = 387) were followed for four years and compared with a retrospective control group (n = 387). Each patient in the intervention group used a messaging device in the home that was connected by a conventional telephone line. Care coordinators monitored the answers from the devices daily so that early interventions could be made. There were significantly more deaths in the control group (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Previous studies of veterans with chronic conditions who used CCHT have shown lower mortality 24 and healthcare utilization [25][26][27] , as well as improved quality of life 26 and more timely receipt of care 28 . Other work has found increased time to readmission among veterans with heart failure 29 , including a dose-response relationship 30,31 .…”
Section: Va's Care Coordination Home Telehealth (Ccht) Programmentioning
confidence: 98%
“…Previous studies of veterans with chronic conditions who used CCHT have shown lower mortality 24 and healthcare utilization [25][26][27] , as well as improved quality of life 26 and more timely receipt of care 28 . Other work has found increased time to readmission among veterans with heart failure 29 , including a dose-response relationship 30,31 .…”
Section: Va's Care Coordination Home Telehealth (Ccht) Programmentioning
confidence: 98%
“…[56][57][58][59][60][61][62][63][64][65] Of these, five were reported by the same senior author with different coauthors. These VHA studies are presented here in historical order as a set, shown in Table 3.…”
Section: Vha Studiesmentioning
confidence: 99%
“…64 The intervention consisted of an automated electronic messaging device that queried patients about their diabetes symptoms and general health on a daily basis. The device was connected to a regular telephone line monitored by nurse coordinators.…”
mentioning
confidence: 99%
“…Further, we identified a number of welldesigned studies that examined access interventions, but they were not included in our review because they did not include data regarding either actual or perceived access outcomes. [29][30][31][32][33][34][35][36][37][38][39][40] Therefore, there are studies that report on the impact of access interventions on downstream outcomes that are not included in this review. As discussed above, we suggest that future research examining access interventions collect and compare a broad range of perceived and actual access outcomes across groups.…”
Section: 16mentioning
confidence: 99%